Combined morphine-clonidine adjuvant in epidural analgesia support role of supraspinal modulation in opioid tolerant patient - Widnyana, I Made Gede; Cindryani, Marilaeta; Tanggono, Aninda (DiscoverSys Inc., 2019)
ABSTRACT Acute pain patients with complicated pain-related experiences would need more than just a pain reliever, especially those with behavioral opioid usage. Latest findings revolving supraspinal modulation are not only taking experts and pain physician into a different stage of understanding but also making theories and management revisited. A 41-years-old Australian male underwent plate and screw fixation of his right femur. He was overweight with a history of behavioral opioid usage. He was given epidural analgesia for postsurgical management with bupivacaine 0.1% with morphine 2 mg and clonidine 30 mcg every 12 hours as adjuvants. Hemodynamic curves were in normal limits, no paralysis, urinary difficulties, or pruritus. He was discharged on the fourth day. The combined morphine-clonidine adjuvant in epidural analgesia technique was an effective choice to alleviate pain response in this opioid-tolerant patient.